Pemaksimalan Pemasaran Online Produk UMKM Keripik Jahe dan Sagon Kelapa Pada Masa Pandemi Covid-19 - Ratna Tri Hardaningtyas; Anggi Triutami (Jurnal Pengabdian Kepada Masyarakat Kalam, 2022)
MSMEs are one of the business groups that have a fairly large number and survive despite the economic crisis. MSMEs have great potential in national and sectoral economic development. The number of types and products owned by MSMEs so that they have tight competitiveness in direct marketing activities. The use of social media and marketplaces is an opportunity to switch from traditional marketing to modern internet-based or online marketing to reach a wider target market. Amadanom Village is one of the villages that produces agricultural and plantation products, one of which is coffee. In addition to producing agricultural and plantation products, Amadanom Village also has several kinds of MSMEs, one of which is the business of ginger chips and coconut sago. However, business owners are not aware of the importance of using online marketing as a form of marketing in the digital era. The use of the marketplace is an effort to help digitize the role of MSMEs in Amadanom Village, especially the ginger chip business. The methods used in this service are interviews and training. The purpose of this activity is to provide awareness of the importance of online marketing and training to create an account at marketspace. As a result, the business owner already has his own sales account to market his products. With this training and introduction about online marketing, ginger chip business owners in Amadanom Village can be more aware of and improve their production and marketing system.